Volatility of Oil Prices and Public Spending in Saudi Arabia: Sensitivity and Trend Analysis - Ali, Anis (International Journal of Energy Economics and Policy, 2020)
The export of petroleum products is the base avenue and constitutes a major ingredient of the Saudi economy. It is evident that the oil prices gradually decrease year by year governed by some international uncontrollable factors. The study is based on the secondary data obtained from the website of the Saudi Arabian Monetary Authority (SAMA). The study applies the Co-efficient of variation (CV), chain based (ICB) and fixed based (IFB) index numbers, correlation, and line diagram to get variability, movement, co-movement, and sensitivity and trends of the oil prices and dependent public spending avenues. The study reveals that the Saudi government enhances the level of their public spending while the oil prices lowering year by year. There is low positive sensitivity between oil prices and public spending while a negative trend between oil prices and public spending in long run. The shocks of the oil prices affect the public spending maintaining a certain gap between the growth’s trends between of public spending and oil prices progressive order in long run. The trend reveals that the Saudi government basically focuses on education, health, and other community and social services while least on social security & welfare, and housing and community amenities services. Keywords: Oil prices, public spending, sensitivity, trend analysis, Saudi Arabia JEL Classifications: Q40, Q41, I10, I20, I30 DOI: https://doi.org/10.32479/ijeep.10601